Real-world experience with monthly and quarterly dosing of fremanezumab for the treatment of patients with migraine in Japan - Suzuki, Shiho; Suzuki, Keisuke; Shiina, Tomohiko; Haruyama, Yasuo; Hirata, Koichi (Frontiers in Neurology, 2023)
Background The effectiveness of fremanezumab in treating migraine has been demonstrated in randomized controlled trials. However, real-world study results are still limited. Methods We conducted a single-center, observational study that included patients with episodic migraine (EM) and chronic migraine (CM) who received fremanezumab monthly or quarterly over 6-month periods. The primary outcome of this study was to evaluate changes in monthly migraine days (MMD) and responder achievement after treatment with fremanezumab. The secondary aim was to characterize the predictors of responder at 6 months. We also evaluated the effectiveness of fremanezumab in the patients who switched from other calcitonin gene-related peptide (CGRP) monoclonal antibodies, and compared the effectiveness of fremanezumab between the monthly and quarterly dosing groups. One hundred twenty-seven patients with migraine (age, 45.2 ± 12.6 years; 96 women) who received at least one dose of fremanezumab with ≥3 months of follow-up were included. The number of MMD was assessed by headache diary. Results The changes in MMD from baseline at 1, 3, and 6 months were −6.1 ± 4.7, −7.7 ± 4.4, and − 8.5 ± 4.5 days in the total cohort, respectively (p < 0.001). The ≥50%, ≥ 75 and 100% responder rates at 6 months were 67.6, 22.5, and 5.4% in the total cohort, 90.4, 36.5, and 9.6% in the EM group, and 52.2, 14.9, and 1.5% in the CM group, respectively. Fremanezumab was also effective in 35 patients who switched from other CGRP monoclonal antibodies. Quarterly and monthly fremanezumab doses were equally effective in MMD reduction in the EM and CM groups. In the CM group, 65.1% experienced remission to EM after 6 months. Adverse reactions were mild and occurred in 9.5% of total patients. An at least ≥50% reduction in MMD from months 1 to 3 better predicted a ≥ 50% reduction in MMD at 6 months with 90.5% sensitivity and 80.6% specificity (p < 0.001). Conclusion In our real-world study, quarterly and monthly fremanezumab dosing showed both favorable effectiveness and tolerability in patients with migraine.